2023
DOI: 10.3847/1538-4357/acaf7a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Scale Magnetic Reconnection with a Turbulent Forcing: Particle-in-cell Simulations

Abstract: Turbulent magnetic reconnection has been observed by spacecraft to occur commonly in terrestrial magnetosphere and the solar wind, providing a new scenario of kinetic scale magnetic reconnection. Here by imposing a turbulent forcing on ions in particle-in-cell simulations, we simulate kinetic scale turbulent magnetic reconnection. We find formation of fluctuated electric and magnetic fields and filamentary currents in the diffusion region. Reconnection rate does not change much compared to that in laminar Hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…They suggest that wandering field lines could open the exhaust angle, leading to fast reconnection (Matthaeus & Lamkin 1986;Lazarian & Vishniac 1999;Vishniac et al 2012;Lazarian et al 2020). Recent magnetohydrodynamic (MHD) simulations show that external forces driving turbulence facilitate the conversion of magnetic energy into plasma kinetic energy, thereby increasing the reconnection rate (Sun et al 2022), while 2D particle-in-cell (PIC) simulation of reconnection with imposed turbulent force found that turbulence enhances the energy conversion rate but does not obviously increase the reconnection rate (Lu et al 2023). Conversely, 3D PIC simulations demonstrate that the reconnection rate and total energy conversion rate in turbulent reconnection (turbulence driven by reconnection) closely resemble those in laminar reconnection by 2D simulations (Daughton et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that wandering field lines could open the exhaust angle, leading to fast reconnection (Matthaeus & Lamkin 1986;Lazarian & Vishniac 1999;Vishniac et al 2012;Lazarian et al 2020). Recent magnetohydrodynamic (MHD) simulations show that external forces driving turbulence facilitate the conversion of magnetic energy into plasma kinetic energy, thereby increasing the reconnection rate (Sun et al 2022), while 2D particle-in-cell (PIC) simulation of reconnection with imposed turbulent force found that turbulence enhances the energy conversion rate but does not obviously increase the reconnection rate (Lu et al 2023). Conversely, 3D PIC simulations demonstrate that the reconnection rate and total energy conversion rate in turbulent reconnection (turbulence driven by reconnection) closely resemble those in laminar reconnection by 2D simulations (Daughton et al 2014).…”
Section: Introductionmentioning
confidence: 99%